Pengaruh Konsumsi Kopi Terhadap Kejadian Hipertensi : Studi Literatur - meyke herlin indriani (Jurnal Kesehatan Masyarakat Indonesia, 2023)
AbstractIntroduction: Hypertension is one of the most common diseases in the community. Hypertension can be caused by several conditions. Several risk factors for hypertension include major (uncontrollable) and minor (controllable) risk factors. Risk factors that can cause hypertension can be controlled, such as lifestyle and diet. One of the most common bad lifestyles related to hypertension in Indonesia is excessive coffee consumption. Objective: To determine the effect of coffee consumption on the incidence of hypertension. Methods: Literature review was conducted by searching articles through electronic databases (Google Scholar, PubMed, ScienceDirect, and SpringerLink) using the keywords coffee consumption, hypertension, and coffee AND hypertension. The inclusion criteria for the articles used were articles published in accredited national and international publication articles, year of publication of articles in the 2017-2023 range, full text, open access, and research articles. The exclusion criteria were articles with a review article research design. Nine articles were selected for analysis. Articles are analyzed using matrix tables and Prism schemes. Results: Based on the literature review, it was found that coffee consumption affects blood pressure and coffee consumption does not have a significant relationship with hypertension. Conclusion: Coffee consumption has an effect on increasing blood pressure, both systolic and diastolic, so that coffee has an indirect effect on the incidence of hypertension. This happens because of the caffeine content in coffee. However, several studies have shown that there is no significant effect of coffee consumption on hypertension, but that there is an interactive relationship between the two.